Peran Bimbingan Dalam Membantu Siswa SMA Negeri 1 Lembang Mengatasi Kesulitan Belajar Matematika - Neng Siti Nur Sadiyah; Mutiara Azzahra; Levina Lidya Maheswari; Agata Fanny Pakpahan; Ibrahim Al Hakim (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the role of academic guidance and counseling in helping SMA Negeri 1 Lembang students overcome mathematics learning difficulties. The research method used was descriptive qualitative, with the main data obtained through in-depth interviews with students. The results show that academic guidance can improve students' understanding of math learning strategies, although its effectiveness depends on the quality and frequency of guidance. In addition, counseling guidance is proven to help students manage learning stress, especially through a personalized and empathic approach. Individual guidance approaches are more effective in meeting the needs of students with specific learning styles, while group guidance encourages collaboration and self-confidence. Teachers play an important role in creating a supportive learning environment, although some students still face challenges due to cognitive constraints and low motivation. This study concludes that quality mentoring can improve students' confidence, concept understanding and academic performance.